(untitled) (Journal of Health Sciences, 2025)
Dear Editor, I have read the article entitled ''The pain ratio before and after physiotherapy for dysfunction of temporo mandibular joint"' by Hadzic et al. I would like to comment on this article in terms of its strengths, weaknesses and future perspectives. I believe that this additional letter will make this article more comprehensive and interesting.